Sosialisasi Program Anti Bullying Dalam Rangka Menciptakan Sekolah Damai - Djoekardi, Djoemeliarasanti (UI Scholars Hub, 2015)
The phenomena of bullying, particularly in education has happened for a long time. However, for various reasons does not appear on the surface. Bullying has negative effects on its victims. It can affect undesirable traits in a child’s development in the future, especially if they are dominated by negative emotions. In association with schools, an anti- bullying program is needed in order to create a peaceful learning process at schools. This research was conducted at 3 high schools in Jakarta. Based on previous findings, it can be seen that teachers and students does not understand bullying behavior and it’s negative impacts on students. The research aims to provide information and raise awareness on the violence and persecution at schools through a anti-bullying program in order to create a more peaceful environment at schools. A qualitative method was used for this research and an action research type was conducted, which consisted of 3 stages: look, think and act. The result of the anti-bullying socialization showed that there is an increasing understanding of bullying however there are some limitations to minimize bullying at schools. In addition, schools has not implemented specific rules about bullying and requires the cooperation among stakeholders, namely teachers, students and parents in order to create a peaceful school.